SUSTAINABLE CHEMISTRY FOR SUSTAINABLE INDUSTRY - G. Rizzuto; F. Bucelli; M. Sciaccaluga; O. Avataneo (Литьë и металлургия)
Foundry Alfe Chem is an industrial reality working in the field of lubrication and chemical auxiliaries for industrial processes, which falls within the framework of the emerging and increasingly important «green chemistry». The goal of the company is to develop products that are more environmentally friendly by using raw materials from renewable sources; specifically, Foundry Alfe Chem has a program of self-sustainability that contemplates, for the foreseeable future, the direct production of renewable raw materials. The company has developed a new dedicated product line, Olitema, whose purpose is to offer highly technological solutions with complete environmental sustainability. In this context, Foundry Alfe CHEM has created a new product which represents a breakthrough in the class of HFC hydraulic fluids: Ecosafe Plus is a biodegradable fire-resistant hydraulic fluid with high engineering and technological performances, high environmental sustainability and the best security guarantees in workplaces. Its formulation is glycols-free, and it allows for easier disposal of the exhausted fluid, compared to a traditional water/ glycol-based HFC hydraulic fluid. For what concern the technological properties, Ecosafe Plus has been tested by accredited laboratories with tribological trials (4 Ball wear test ASTM D 4172, Ball on disc test ASTM 6425, Brugger test DIN 51347, Vickers test ASTM D 2882), with elastomer compatibility test (ASTM D 471) and biodegradability test (OECD 310 F).